Borehole Microseismic Imaging of Hydraulic Fracturing: A Pilot Study on a Coal Bed Methane Reservoir in Indonesia - Rexha Verdhora Ry; Tepy Septyana; Sri Widiyantoro; Andri Dian Nugraha; Arii Ardjuna (Institute for Research and Community Services, Institut Teknologi Bandung, 2019)
Over the last decade, microseismic monitoring has emerged as a considerable and capable technology for imaging stimulated hydraulic fractures in the development of unconventional hydrocarbon resources. In this study, pilot hydraulic-fracturing treatments were operated at a coal-bed methane (CBM) field in Indonesia to stimulate the flow and increase the reservoir's permeability while the monitoring system was set in a single near-vertical borehole. Locating event sources accurately is fundamental to investigating the induced fractures, but the geometry of a single downhole array is a challenging data processing task, especially to remove ambiguity of the source locations. The locating procedure was reviewed in 3 main steps: (i) accurate picking of P- and S-wave phases; (ii) inclusion of P-wave particle motion to estimate the back azimuth; (iii) guided inversion for hypocenter determination. Furthermore, the seismic-source moment magnitudes were calculated by employing Brune's model. Reliable solutions of locations were obtained as shown statistically by uncertainty ellipsoids and a small misfit. Based on our results, both induced and triggered seismicity could be observed during the treatments and therefore conducting intensive monitoring is important. The triggered seismicity is an undesired activity so disaster precautions need to be taken, in particular for preventing reactivation of pre-existing faults.